Mechanistic analysis of asphalt pavements, using superpave shear tester and hamburg wheel-tracking device - Wang, Jian-Neng (Transportation Research Board of the National Academies, 2007)
Resumen: Presenta una evaluación comparativa de la deformación permanente y del daño de la humedad de las mezclas asfálticas con el probador de corte Superpave y Hamburg wheel-tracking device (HWTD)